2011
DOI: 10.1111/j.1365-2664.2011.01958.x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive management and targeting of agri-environment schemes does benefit biodiversity: a case study of the corn bunting Emberiza calandra

Abstract: Summary1. Agri-environment schemes (AES) are the main European policy response to biodiversity loss caused by agricultural intensification. Maximizing their effectiveness is a key policy challenge. Monitoring is essential to inform adaptation and improvement of schemes over time, and to understand how measures may need to vary across a species' range. 2. We measured changes in breeding abundance of a severely declining bird, the corn bunting Emberiza calandra, in response to AES in Scotland over 7 years and 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
113
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 37 publications
2
113
0
3
Order By: Relevance
“…Another recurrent theme was the need for improved advice on appropriate management and meaningful monitoring programmes linked closely to the objectives which have been set -sentiments that echo findings in other recent studies (e.g. Hart et al 2011;Perkins et al 2011;Armsworth et al 2012).…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Another recurrent theme was the need for improved advice on appropriate management and meaningful monitoring programmes linked closely to the objectives which have been set -sentiments that echo findings in other recent studies (e.g. Hart et al 2011;Perkins et al 2011;Armsworth et al 2012).…”
Section: Discussionmentioning
confidence: 52%
“…For example, in the case of farmland birds, Perkins et al (2011) report how bespoke monitoring was used to assess the effectiveness of a specific scheme in Scotland whilst Baker et al (2012) use more routinely collected monitoring data to identify spatial variation in scheme impacts across the UK. For more complex schemes involving multiple potential benefits, Mauchline et al (2012) and Pannell et al (2013) separately advocate the involvement of scheme participants in not only scheme design but also in undertaking monitoring activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some AESs have substantially benefitted target species (e.g. Aebischer et al 2000, Peach et al 2001, Albrecht et al 2007, Perkins et al 2011 while others have shown no demonstrable benefit to target species or overall biodiversity (e.g. Kleijn et al 2001, Kleijn et al 2004, Davey et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggested that adaptive management, or 'learning through doing' (Convention on Biological Diversity 2004), is a key tool to improve the biodiversity benefits from AESs (Perkins et al 2011) by encouraging modification of AESs to improve their benefit for wildlife as new information comes to light.…”
Section: Introductionmentioning
confidence: 99%